2019
DOI: 10.1186/s12955-019-1105-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and measurement properties of the Nepali version of the DASH (disability of arm, shoulder and hand) in patients with shoulder pain

Abstract: BackgroundPatient-reported outcome measures (PROMs) are important tools in both clinical practice and research. However, no upper extremity PROM to assess physical disability is available in Nepali. The most commonly used and recommended questionnaire for the shoulder is the Disability of Arm, Shoulder and Hand (DASH). Therefore, the aim of the study was to translate and cross-culturally adapt the DASH into Nepali and determine its measurement properties.MethodsThe translation and cultural adaptation process f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…We were unable to analyze reliability separately for face-to-face and telephone interviews. In a previous and similar validation study, we found no differences in test-retest reliability of the Nepali Disability of Arm, Shoulder, and Hand Questionnaire [ 56 ]. Further studies may assess the reliability separately for face-to-face administration of CSI-NP.…”
Section: Discussionmentioning
confidence: 49%
“…We were unable to analyze reliability separately for face-to-face and telephone interviews. In a previous and similar validation study, we found no differences in test-retest reliability of the Nepali Disability of Arm, Shoulder, and Hand Questionnaire [ 56 ]. Further studies may assess the reliability separately for face-to-face administration of CSI-NP.…”
Section: Discussionmentioning
confidence: 49%
“…Similarly, another instrument with reverse coded items, the Life Orientation Test -Revised (LOT-R) [42], has been translated into Nepali and found to be poorly interpreted reflected by poor internal consistency in a large sample. We have had good success in translation of PROMs to produce reliable and valid instruments in Nepali in the past for the PROMs which do not have reverse coded response options [33][34][35][36][37][38][39][40]. Simplifying PROMs for target populations with low-levels of literacy, such as Nepali, is very important because the participants' ability to interpret the meaning of the and responses is dependent on educational level of the individual [35,43].…”
Section: Discussionmentioning
confidence: 99%
“…The translation project manager (TPM), the lead author of the paper (SS), performed a thorough review of all translations. The TPM also has a great deal of experience translating, cross-culturally validating PROMs from English into Nepali[33][34][35][36][37][38][39][40]. The TPM noted the consistencies and discrepancies in the translations and added notes or comments for the reviewers (see below) and the PROMIS instrument developer representative to consider.Three independent reviews.…”
mentioning
confidence: 99%
“…The DASH is reported being valid, reliable, and responsive for patients with shoulder pain. 2 , 13 , 40 , 41 The DASH 7 is reported responsive for patients with subacromial pain with an effect size (Cohens d ) of 0.93. 34 …”
Section: Methodsmentioning
confidence: 99%